Advanced Functional Materials and Cell‐Based Therapies for the Treatment of Ischemic Stroke and Postischemic Stroke Effects. (30th October 2019) - Tapeinos, Christos; Larrañaga, Aitor; Tomatis, Francesca; Bizeau, Joëlle; Marino, Attilio; Battaglini, Matteo; Pandit, Abhay; Ciofani, Gianni
Abstract: Ischemic stroke is considered one of the most threatening neurological disorders with high percentages of mortality and morbidity worldwide. Although in recent years, several nanotechnological advances have improved the survival rates, severe untreated poststroke side‐effects continue to significantly influence the way of life of many. Tissue plasminogen activator and mechanical thrombectomy are considered the gold standards for the treatment of acute cerebral ischemia. These, however, fail to improve postischemic disorders. Herein, after a brief description of the pathophysiology of ischemic stroke and the following biochemical cascade, the most recent biomaterial and cell‐based strategies are reviewed for its treatment. Other therapeutics that have been proposed not only for the treatment of cerebral ischemia but also for the regeneration of the infarcted brain that is responsible for a variety of disorders, including cognitive, motor, and speech problems are also presented. Finally, a few reported studies on diagnostic and theranostic nanostructures are also provided. Abstract : Ischemic stroke occurs when an artery supplying blood to the brain is obstructed, leading to the death of neuronal cells and severe post‐stroke side effects. A number of biomaterial‐ and cell‐based approaches have been studied as potential stroke therapeutics. In this work, a summary of the most important of these nanotherapeutics (polymers, lipids, peptides, hydrogels, stem cells, and others) is presented.